Vic9 mycobacteriophage: the first subcluster B2 phage isolated in Russia - Zaychikova, Marina; Malakhova, Maja; Bespiatykh, Dmitry; Kornienko, Maria; Klimina, Ksenia; Strokach, Aleksandra; Gorodnichev, Roman; German, Arina; Fursov, Mikhail; Bagrov, Dmitry; Vnukova, Anna; Gracheva, Alexandra; et al. (Frontiers in Microbiology, 2025)
Mycobacteriophages are viruses that specifically infect bacteria of the Mycobacterium genus. A substantial collection of mycobacteriophages has been isolated and characterized, offering valuable insights into their diversity and evolution. This collection also holds significant potential for therapeutic applications, particularly as an alternative to antibiotics in combating drug-resistant bacterial strains. In this study, we report the isolation and characterization of a new mycobacteriophage, Vic9, using Mycobacterium smegmatis mc (2)155 as the host strain. Vic9 has been classified within the B2 subcluster of the B cluster. Morphological analysis revealed that Vic9 has a structure typical of siphophages from this subcluster and forms characteristic plaques. The phage adsorbs onto host strain cells within 30 min, and according to one-step growth experiments, its latent period lasts about 90 min, followed by a growth period of 150 min, with an average yield of approximately 68 phage particles per infected cell. In host range experiments, Vic9 efficiently lysed the host strain and also exhibited the ability to lyse M. tuberculosis H37Rv, albeit with a low efficiency of plating (EOP ≈ 2 × 10−5), a typical feature of B2 phages. No lysis was observed in other tested mycobacterial species. The genome of Vic9 comprises 67,543 bp of double-stranded DNA and encodes 89 open reading frames. Our analysis revealed unique features in Vic9, despite its close relationship to other B2 subcluster phages, highlighting its distinct characteristics even among closely related phages. Particularly noteworthy was the discovery of a distinct 435 bp sequence within the gene cluster responsible for queuosine biosynthesis, as well as a recombination event within the structural cassette region (Vic_0033-Vic_0035) among members of the B1, B2, and B3 subclusters. These genetic features are of interest for further research, as they may reveal new mechanisms of phage-bacteria interactions and their potential for developing novel phage therapy methods.